Huge adenomyotic cyst in pregnancy - Raimi ZH,; Ng, Beng Kwang; Omar MH,; Lim, Pei Shan (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
Adenomyotic cyst is a rare variant of adenomyosis. It is believed to arise from repeated focal haemorrhages resulting in cystic spaces filled with altered blood products. We present a rare case of a huge adenomyotic cyst in a 27-year-old primigravida, who was in her first trimester, complaining of sudden lower abdominal pain. Diagnostic laparoscopy performed to rule out other cause of acute abdomen. Her pregnancy went on smoothly. She delivered a baby girl of 2.82 kg via vaginal delivery at 39 weeks. Diagnosis and management of this rare clinical entity were reviewed and discussed.